2019
DOI: 10.1038/s41598-019-43678-6
|View full text |Cite
|
Sign up to set email alerts
|

EGFR and HER3 expression in circulating tumor cells and tumor tissue from non-small cell lung cancer patients

Abstract: Although clinically relevant, the detection rates of EpCAM positive CTCs in non-small cell lung cancer (NSCLC) are surprisingly low. To find new clinically informative markers for CTC detection in NSCLC, the expression of EGFR and HER3 was first analyzed in NSCLC tissue (n = 148). A positive EGFR and HER3 staining was observed in 52.3% and 82.7% of the primary tumors, and in 62.7% and 91.2% of brain metastases, respectively. Only 3.0% of the brain metastases samples were negative for both HER3 and EGFR protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 35 publications
0
66
0
Order By: Relevance
“…In NSCLC, HER3-overexpression has been reported in 80% of EGFR-mutated adenocarcinomas [ 78 ]. HER3-DXd demonstrated to inhibit tumor growth in HER3+, EGFR-mutated, EGFR-TKI resistant patient-derived xenograft (PDX) models, while it was ineffective in HER3-negative models [ 79 ].…”
Section: Promising New Targets Under Investigationmentioning
confidence: 99%
“…In NSCLC, HER3-overexpression has been reported in 80% of EGFR-mutated adenocarcinomas [ 78 ]. HER3-DXd demonstrated to inhibit tumor growth in HER3+, EGFR-mutated, EGFR-TKI resistant patient-derived xenograft (PDX) models, while it was ineffective in HER3-negative models [ 79 ].…”
Section: Promising New Targets Under Investigationmentioning
confidence: 99%
“…Several studies demonstrated that these proteins are upregulated in metastatic tissue and in CTCs compared to the primary tumor [9]. The authors concluded that the combination of EGFR/HER3 enrichment with the EpCAM-based CellSearch technique may detect a significantly higher number of CTCs in NSCLC patients by liquid biopsy [10].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Such studies with the Her/EGFR-targeted capture based on heterogeneous expression in cells have been previously demonstrated. 45 Subsequently, we conducted a specificity test for FeNC−Her and FeNC−EGF in capturing positive target cells relative to control from a cell mixture in serum. For this experiment, we used samples spiked with an A549−HCC827 1:1 mixture (from 10 2 to 10 4 cells per cell line), wherein A549 was a positive control for FeNC−Her, and HCC827 was a negative control.…”
Section: ■ Results and Discussionmentioning
confidence: 99%